2014
DOI: 10.1007/s12155-014-9568-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Acid Hydrolysis of Jerusalem Artichoke-Derived Inulin for Fermentative Butanol Production

Abstract: In this study, a central composite design and response surface methodology were used to study the effect of various hydrolysis variables (temperature, pH, and time) on the acid hydrolysis of Jerusalem artichokederived inulin using three different mineral acids (HCl, H 2 SO 4 , and H 3 PO 4 ). Numerical optimization was used to maximize the sugar yield of Jerusalem artichoke powder within the experimental range for each of the mentioned acid. The influence of each acid on the formation of hydroxymethylfurfural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 31 publications
(57 reference statements)
0
28
0
Order By: Relevance
“…Jerusalem artichoke (JA) that can grow well in marginal lands is a potential energy crop for biorefinery, and its major biomass is from tubers with inulin as a major carbonhydrate, which can be easily hydrolyzed into a mixture of fructose and glucose at a ratio of %4:1 (w/w). [9,10] JA tubers have been successfully applied for microbial fermentation to produce 2,3-butanediol, lactate, butyrate, and ethanol. [11][12][13][14] However, barriers remain to be addressed for butanol production by C. acetobutylicum from JA tubers due to insufficient fructose utilization, unfavorable acidification, extended lag phase, and poor butanol production and yield.…”
Section: Introductionmentioning
confidence: 99%
“…Jerusalem artichoke (JA) that can grow well in marginal lands is a potential energy crop for biorefinery, and its major biomass is from tubers with inulin as a major carbonhydrate, which can be easily hydrolyzed into a mixture of fructose and glucose at a ratio of %4:1 (w/w). [9,10] JA tubers have been successfully applied for microbial fermentation to produce 2,3-butanediol, lactate, butyrate, and ethanol. [11][12][13][14] However, barriers remain to be addressed for butanol production by C. acetobutylicum from JA tubers due to insufficient fructose utilization, unfavorable acidification, extended lag phase, and poor butanol production and yield.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that as compared to HCl, H3PO4, sulfuric acid (H2SO4) had a positive impact on diluted mineral acid catalyzed the hydrolysis of cellulose Sarchami & Rehmann, 2015). Thus, for the current investigation, H2SO4 has considered for dilute mineral acid catalyzed the hydrolysis of the waste sample.…”
Section: Acid Mediated Heating Experiments On Sugar Removal From Wastementioning
confidence: 99%
“…[44] Acid hydrolysis is a simple pretreatment to obtain fructose from inulin and the catalyst can be HCl, H 2 SO 4 , or H 3 PO 4 . [45] Microbial inulinases act on the -2,1 bonds of inulin molecules and are categorized into endo-inulinase or exo-inulinase based on the action pattern. [46] The inulin powder was hydrolyzed by sample of fructooligosaccharide (lane 2).…”
Section: Acidic Hydrolysis and Enzymatic Hydrolysis Of Inulinmentioning
confidence: 99%
“…In previous studies, it was reported that acid hydrolysis of inulin at high temperature resulted in the formation of 5-hydroxymethylfurfural (HMF), a known by-product and inhibitor for some microorganisms. [45,47]…”
Section: Growth With Acidic or Enzymatic Hydrolyzates Of Inulinmentioning
confidence: 99%